An Afrocentric critique of France's foreign policy towards Africa : case study of South Africa, 2009-2019 - Sethole, Florence Ramasela (My University, 2021)
The relations between France and South Africa dates to +-330 years ago but the year that France renounced its diplomatic collaboration with South Africa was in 1981. Then in 1994 following the new democratic dispensation in South Africa, France started normalising its diplomatic relations with the new government. By the end of 1994 South Africa had France as its 14th biggest trading partner with a total trade of R3712 millions. Moving from that, the central question grappled within this research is that is the relations between France and South Africa a win-win or win-lose one? This research argues that is it a win-lose as France is the one that continues to benefit more compared to South Africa on various partnership which will be discussed further in the research. With regards to the theoretical framework, Afrocentricity was deemed suited as it gives Africans the platform to view issues through African experiences and perspective. The latter should also be understood within the context that a lot of literature on the topic at hand has been written using Eurocentric perceptive thus this research utilised Afrocentricity. Methodologically, this research will be solely relaying on secondary materials such as journal articles, newspapers as well as policy briefs and reports.
Thesis (M. A. (International Politics)) -- University of Limpopo, 2021
Keywords: France; South Africa; Afrocentricity; Foreign Policy; Africa; International economic relations; Investments, Foreign -- France -- Government; Investments, Foreign -- South Africa -- Government